2015
DOI: 10.1371/journal.pone.0128920
|View full text |Cite|
|
Sign up to set email alerts
|

Significant Reductions in Mortality in Hospitalized Patients with Systemic Lupus Erythematosus in Washington State from 2003 to 2011

Abstract: BackgroundSystemic lupus erythematosus (SLE or lupus) is an autoimmune multisystem disease. While a complete understanding of lupus’ origins, mechanisms, and progression is not yet available, a number of studies have demonstrated correlations between disease prevalence and severity, gender, and race. There have been few population based studies in the United StatesObjectivesTo assess temporal changes in demographics and hospital mortality of patients with lupus in Washington State from 2003 to 2011Study Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 27 publications
(43 reference statements)
4
19
0
Order By: Relevance
“…Fig 1 presents a flow chart of the selection process. This study used a population-based cohort study design [ 28 ] and ICD-9-CM codes to define the status of SLE (ICD-9-CM code 710.0) [ 29 ], and incident respiratory failure (ICD-9-CM codes 518.81, 518.83, and 518.84). In Taiwan, patients with chronic inflammatory diseases, including those with SLE, can apply for a catastrophic illness certificate; in addition, patients with SLE who fulfill 4 or more diagnostic criteria based on the American College of Rheumatology criteria are eligible for this certificate [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Fig 1 presents a flow chart of the selection process. This study used a population-based cohort study design [ 28 ] and ICD-9-CM codes to define the status of SLE (ICD-9-CM code 710.0) [ 29 ], and incident respiratory failure (ICD-9-CM codes 518.81, 518.83, and 518.84). In Taiwan, patients with chronic inflammatory diseases, including those with SLE, can apply for a catastrophic illness certificate; in addition, patients with SLE who fulfill 4 or more diagnostic criteria based on the American College of Rheumatology criteria are eligible for this certificate [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…We identified hospitalizations of patients aged ≥ 18 years between the years 2009 and 2014 with a diagnosis of SLE, based on the presence of International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) code 710.0 in the principal or secondary diagnosis fields. This code was validated in administrative data, with sensitivity of 79.3%, specificity of 90.2%, and with a positive predictive value of 95.9% [27], and was used in prior studies of SLE [28,29]. Hospitalizations with sepsis were identified by the presence of either (a) a combination of ICD-9-CM codes for infection and one or more organ dysfunctions, as described by Angus et al [30], or (b) "explicit" codes for severe sepsis (995.92) or septic shock (785.52).…”
Section: Data Sources and Study Populationmentioning
confidence: 99%
“…Studies have shown that the disproportionate burden of lupus among AAs negatively affects quality of life 7276 and coping ability. 77 Some have positioned elevated rates of SLE in AA women in the context of “immune cognition”.…”
Section: Introductionmentioning
confidence: 99%